2019
DOI: 10.1039/c9cc03958a
|View full text |Cite
|
Sign up to set email alerts
|

An efficient dynamic asymmetric catalytic system within a zinc-templated network

Abstract: Enhanced cooperativity leading to high catalytic activity and stereoselectivity in the direct aldol reaction has been achieved through a complex network of simple species interacting reversibly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…17). 90 We demonstrated that the complex network thus generated, with several potential catalysts, actually simplified under the reaction conditions making the bifunctional species to predominate in a kind of thermodynamic self-sorting. As expected, this species also provided the highest reaction acceleration and stereoselectivity, improving the performance of the previous pyridine-based system at lower catalyst loading.…”
Section: Complex Systems Leading To Efficient Catalysismentioning
confidence: 91%
See 1 more Smart Citation
“…17). 90 We demonstrated that the complex network thus generated, with several potential catalysts, actually simplified under the reaction conditions making the bifunctional species to predominate in a kind of thermodynamic self-sorting. As expected, this species also provided the highest reaction acceleration and stereoselectivity, improving the performance of the previous pyridine-based system at lower catalyst loading.…”
Section: Complex Systems Leading To Efficient Catalysismentioning
confidence: 91%
“…Moreover, its reversible nature made impossible the synthesis and isolation of the catalytic complex, and the network generated with the three-components mixture was a convenient (and actually the only) manner of utilizing it. 90 Thus, our approach illustrated how a dynamic system can cooperatively work for the formation of an active catalyst, even in the presence of other species in equilibrium, which are intrinsically needed for the function of the system.…”
Section: Complex Systems Leading To Efficient Catalysismentioning
confidence: 99%
“…(the syn diastereomer predominated), and the ee was moderate (Table , entry 7). Additionally, acetone was also used affording final aldol product with excellent yield but modest ee (Table , entry 8) …”
Section: Internal or External Lewis Acid Assisted (Thio)urea Catalmentioning
confidence: 99%
“…We have previously investigated reaction networks of so-called dynamic covalent catalysts. [22][23][24][25][26] By connecting catalytically active components with reversible imine bonds (Figure 1a), catalysts capable of modifying their own molecular architecture are accessible. When incorporated into dynamic systems undergoing constitutional exchange, these compounds display self-resolving behavior.…”
Section: Introductionmentioning
confidence: 99%